Benign Natural History of Spondylolysis in Adolescence With Midterm Follow-Up - Sousa, Ted, MD; Skaggs, David L., MD, MMM; Chan, Priscella, MS; Yamaguchi, Kent T., MD; Borgella, Jerald, BS; Lee, Christopher, MD; Sawyer, Jeffrey, MD; Moisan, Alice, RN; Flynn, John M., MD; Gunderson, Melissa, BA; Hresko, M. Timothy, MD; D'Hemecourt, Pierre, MD; et al. (Spine deformity, 2017)
Abstract Study Design Retrospective chart review. Objectives To use the Micheli Functional Scale to assess adolescent patients with spondylolysis treated conservatively at midterm follow-up. Summary of Background Spondylolysis is a common source of back pain for adolescents and is generally managed with bracing and physical therapy. There is little data regarding the results of conservative management of spondylolysis over time. Methods Four major academic pediatric institutions performed a retrospective chart review of patients from 5 to 21 years of age with the initial diagnosis of spondylolysis. Inclusion criteria were patients who initially underwent conservative management and had a minimum of 2 years' follow-up. The patients were contacted and asked to complete the Micheli Functional Scale Survey. Results A total of 295 patients with the diagnosis of spondylolysis were identified and contacted. Sixty-one subjects with spondylolysis completed the follow-up survey. Sixty of 61 respondents (98%) answered questions regarding their current pain level. Thirty-five of 60 (58.3%) reported no pain (0/10) and 47/60 (78%) rated their pain at 3 or less, whereas 22% (13/60) rated their pain as 4 or higher. There was no correlation with pain ratings on the follow-up survey and radiographic healing at initial management. Of the 61 patients, 50 returned to sports (82%), 8 did not return (13%), and 5 returned to most but not all of their sports (8%). No correlation was observed between radiographic healing and return to sports (p = .4885). Conclusion Using a validated functional scale, this study demonstrated that with conservative management of spondylolysis a majority of patients at an average of 8 years out self-report a return to sports (90%), though many reported continued pain (42%) and interference with activities (67%). There was no correlation observed between radiographic evidence of healing and pain or return to sports with a mean follow-up of 8 years. Level of Evidence Multicenter retrospective case series.